P3 Porto-mesenteric thrombosis in a non-cirrhotic patient with SARS-CoV-2 infection. (28th September 2020) - Abeysekera, Kushala; Gitahi, Jane; Flood, Richard; Sudlow, Alexis; Lyen, Stephen; Clark, Amanda; Gordon, Fiona
Abstract : Introduction: During the coronavirus 2019 (COVID-19) pandemic, it is clear this novel coronavirus generates a markedly hypercoagulable state. Thrombotic events are driven by a severe pro-inflammatory response to COVID-19 as well as hypoxia manifested in severe illness. Whilst the commonest thrombotic events associated with COVID-19 remain pulmonary embolism, myocardial infarction and deep vein thrombosis, intra-abdominal thromboses are less well characterised, but are illustrated in this case. Case Presentation: A 42 year-old Eastern European man with chronic hepatitis B (undetectable viral load on Entecavir; eAg negative; sAg positive; alanine transaminase (ALT) 34 IU/l; FibroScan 7.4kPa Nov 2019), and prior trauma-related splenectomy (1998), developed pyrexia and cough on the 23rd March 2020. His fever resolved on symptom-day 10, following a course of Amoxicillin, then Doxycycline, for presumed bronchitis from his GP. On symptom day 14, he woke with constant non-radiating right hypochondrial pain. The following day he presented to his local hospital and was managed conservatively for suspected biliary colic (no imaging). His bilirubin was 23µmol/l, ALT 55 IU/l, alkaline phosphatase (ALP) 66 IU/l and albumin 31 g/l. Having been discharged with analgesia, he re-presented to his GP with ongoing worsening pain on symptom-day 25. His bilirubin was now 33µmol/l, ALT 31 IU/l, ALP 74 IU/l and albumin 35 g/l. Abdominal ultrasound suggested portal vein thrombosis (PVT) with collateralisation. He was subsequently admitted by the general surgeons and a CT-abdomen demonstrated loss of enhancement of the entire length of the portal vein and proximal superior mesenteric vein, with expansion and surrounding inflammatory stranding consistent with thrombosis. Concurrent CT-chest demonstrated bilateral patchy ill-defined ground glass opacities with basal predominance, worse on the right, consistent with COVID-19 infection. Whilst his RT-PCR was negative, subsequent SARS-CoV-2 antibody serology was positive. His thrombophilia screen excluded inherited and acquired thrombophilia such as antiphospholipid syndrome. His repeat triple phase CT-abdomen 6 weeks later, confirmed an established PVT with collateralisation extending into the upper abdomen. Having been commenced on Apixaban 5 mg BD in April 2020, he is currently asymptomatic. Discussion: This is one of the first cases of likely COVID-19-related porto-mesenteric thrombosis to be described in the UK. Similar cases have been described in France and Italy in non-cirrhotic patients. With almost a fifth of COVID-19 infections presenting with gastrointestinal symptoms, and a recent meta-analysis suggesting 9.2% developing abdominal pain, our threshold for performing liver ultrasound with doppler assessment must be lower to avoid missing this reversible complication of COVID-19.